Assessing the risk of reoperation for mild pulmonary vein obstruction post-TAPVC repair: a retrospective cohort study - Alifu, Ailixiati; Wang, Haifan; Chen, Renwei (Frontiers in Cardiovascular Medicine, 2024)
Objective: This study investigates the impact of mild pulmonary vein obstruction, detected via echocardiography before hospital discharge, on the likelihood of reoperation in patients who have undergone repair for Total Anomalous Pulmonary Venous Connection (TAPVC). Method: Utilizing a single-center, retrospective cohort approach, we analyzed 38 cases from October 2017 to December 2023, excluding patients with functionally univentricular circulations or atrial isomerism. Our primary outcome was the necessity for reoperation within one year due to anatomical issues related to the initial TAPVC repair. Mild obstruction was defined as a pulmonary vein flow velocity≥1.2 m/s. Result: Our findings revealed that 31.6% of patients exhibited pre-discharge mild obstruction. During the median follow-up of 10 months, reoperations were notably higher in the mild obstruction group compared to the normal group, with a significant association between pre-discharge mild obstruction and increased risk of reoperation. Specifically, in the fully adjusted model, mild obstruction was linked to a 13.9-fold increased risk of reoperation. Conclusion: Our results suggest that a pre-discharge echocardiography Doppler velocity threshold of 1.2 m/s could serve as a critical predictor for reoperation, emphasizing the need for targeted follow-up strategies for at-risk patients.